Pemberdayaan Pelaku Usaha Untuk Meningkatkan Jumlah Produksi Dan Mutu Pada Nutrisi Telur Asin Oleh Penggiat Home Industri - Mislan Mislan; Rahmita Sari; Dedy Khaerudin (Pusat Riset dan Inovasi Nasional, 2024)
The village of Sendal Kopo is the village of Panenjoan in the Serang district of Banten Province, where people produce salted eggs. However, a problem faced in making this salty egg is the need for more marketing of products and the quality of nutrition in the salty egg, which is affecting the production. Therefore, an increase in the production and quality of salt egg nutrition results in increased production and income for business people. The method used for community dedication is the participative method of training the home industry in the village of Panenjoan. This activity takes place for one (1) month, and the training given goes smoothly, smoothly as well as orderly. As a result of this activity, the coal-fired home industry can increase production and the quality of salted egg nutrition as the volume of salted egg production increases.